KESATUAN AGAMA DALAM PERSPEKTIF TASAWUF - Hasyim (PUSAT PENELITIAN DAN PENGABDIAN MASYARAKAT (P3M) SEKOLAH TINGGI ILMU TARBIYAH AL-FATTAH SIMAN LAMONGAN, 2019)
Mysticism does not consider what religion is embraced by the mysticist. This religious phenomenon is found not only in the three given religions, but also found in other religions. There must be interactions and conflicts. Since the essence of mysticism is the awareness of the existence of communication and direct dialog between human being and God, in the practice it emphasizes more on the ‘hakekat’ than ‘lahiriyah’. The idea of Wahdah al-Adyan, according to al-Hallaj, explains that religions taught by the prophets come and will be back to the one source. There are differences among religious teachings, but it is only on names and forms. It has the same goals, that is how to worship God.